High-flexibility modified silicate as well as preparation method and application thereof
By modifying silicates with polyamine polymers with epoxy silanes and alkyl silanes, the flexibility and stability of aqueous inorganic coatings are solved, compatibility with polymer emulsions is improved, and efficient coating is achieved Film formation and crack resistance.
Patent Information
- Application Number
- CN202310847530.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-14
AI Technical Summary
Water-based inorganic coatings have problems such as slow drying speed, large rigidity of coatings and easy cracking, and the polymer emulsion is not compatible with silicates, which limits its application range.
The flexibility and stability of inorganic silicate coatings are improved by reacting polyamine polymer with epoxy silane and alkyl silane with silicates, and the polyamine polymer is used to form a highly flexible modified silicate. Complexation of polyvalent metal ions in the acid salt solution enhances storage stability.
提高了无机硅酸盐涂料的柔韧性和稳定性,增强了与聚合物乳液的相容性,延长了涂料漆膜的使用寿命,并在不添加聚合物乳液的情况下保持良好的成膜性 and crack resistance.
Smart Images

Figure BDA0004332975700000031 
Figure BDA0004332975700000061 
Figure BDA0004332975700000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating industry and relates to a highly flexible modified silicate, a preparation method and application thereof. Background Art
[0002] Waterborne inorganic coatings are engineering materials prepared with silicates, phosphates, silica sols, etc. as binders, and different pigments, fillers, additives or curing agents. They are green and environmentally friendly, low cost, and have excellent properties such as high temperature resistance and corrosion resistance. With the improvement of people's environmental awareness and the improvement of coating industry standards, waterborne inorganic coatings have gradually shown huge market potential and economic, social and ecological comprehensive benefits, which has attracted widespread attention. However, waterborne inorganic coatings have defects such as slow drying speed, high coating rigidity and easy cracking, which limits their scope of application. At present, although the performance of inorganic coatings can be improved by adding polymer emulsions, the poor compatibility of polymer emulsions with silicates and phosphates has become another problem that needs to be solved urgently.
[0003] Patent CN115124666A discloses an acrylic acid-potassium silicate copolymer emulsion, and is used to prepare inorganic coatings. The chemical copolymerization structure between potassium silicate and polyacrylic acid makes the inorganic phase and the organic phase more dispersed, which can increase the weather resistance of the inorganic coating film and reduce the amount of organic matter. However, the ester chemical bond of polyacrylic acid is easily hydrolyzed in the strong alkaline environment of potassium silicate solution, and the structural stability is low. Patent CN113881259A discloses an inorganic coating prepared by modified potassium silicate, silica sol and styrene acrylic emulsion. Among them, the modified potassium silicate is modified by an amphiphilic surfactant, so that the number of silanol groups in potassium silicate is reduced and the reaction activity is reduced, and more styrene acrylic emulsion is required to form an effective film. Patent CN114196243A discloses an ethylamine or quaternary ammonium salt modified potassium silicate solution, and the cations of the quaternary ammonium salt or ethylamine can be exchanged with potassium ions in the solution, increasing the steric hindrance of the silanol group and providing the stability of the inorganic coating. However, the interaction between quaternary ammonium salts or ethylamine small molecules and potassium silicate is only a charge interaction, the binding force is weak, the stability is poor, and it is easy to precipitate from inorganic paints or coatings, and the environmental protection is poor. Summary of the invention
[0004] In order to solve the technical problem of poor compatibility between polymer emulsion and silicate in the prior art, the present invention provides a highly flexible modified silicate and a preparation method thereof, and provides the application of the highly flexible modified silicate for preparing water-based inorganic coatings. The modified silicate is formed by chemical bonding of silicate with silane and polyamine polymers. The modified silicate is applied to water-based inorganic coatings, which improves the flexibility and stability of inorganic silicate coatings and solves the problem of poor compatibility between inorganic silicate coatings and polymer emulsions. In addition, the polyamino structure can effectively complex polyvalent metal ions in silicate solutions, thereby improving the storage stability of inorganic coatings. The technical solutions provided by the present invention are as follows:
[0005] A highly flexible modified silicate, which is prepared by reacting a polyamine polymer, epoxy silane and silicate, and then hydrophobically modifying the surface of the silicate with an alkyl silane; wherein the epoxy group in the epoxy silane is connected with the amine group in the polyamine polymer by reaction, the silanol group in the epoxy silane is connected with the silanol group in the silicate by reaction, and the alkyl silane is hydrolyzed and condensed with the hydroxyl group on the surface of the silicate particles;
[0006] The polyamine polymer is a primary amine or secondary amine polymer;
[0007] The epoxysilane is an alkoxysilane containing a glycidyl ether structure;
[0008] The alkylsilane is a trialkoxysilane;
[0009] The mass ratio of the polyamine polymer to epoxy silane is 1:1 to 1:6; the mass ratio of the polyamine polymer, alkyl silane and silicate is 0.2 to 2:0.5 to 1.5:100.
[0010] The average viscosity of the highly flexible modified silicate is 30 to 50 KU.
[0011] Furthermore, the polyamino polymer is one or more of polyethyleneimine, polyallylamine and derivatives thereof, and has a molecular weight of 400 to 9000 kg / mol.
[0012] Furthermore, the epoxysilane is one or more of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-glycidyloxypropyltriisopropoxysilane, γ-glycidyloxypropylmethyldimethoxysilane or γ-glycidyloxypropylmethyldiethoxysilane.
[0013] Furthermore, the structural formula of the alkylsilane is R 1 Si(OR 2 ) 3 , where R 1 is an alkyl group with no more than 4 carbon atoms, R 2 It is methyl or ethyl.
[0014] Furthermore, the alkylsilane is one or more of methyltrimethoxysilane, methyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, chloropropyltrimethoxysilane or chloropropyltriethoxysilane.
[0015] Furthermore, the silicate is sodium silicate or potassium silicate.
[0016] The present invention also provides a method for preparing the highly flexible modified silicate, which specifically comprises the following steps:
[0017] The polyamine polymer is dissolved in water, and a silicate solution is added thereto, mixed evenly and heated to 40-80° C.; epoxy silane is added, reacted for 2-4 hours, and then alkyl silane is added, and the reaction is continued for 2-4 hours to obtain the aqueous solution of the highly flexible modified silicate.
[0018] The silicate solution has a solid content of 20 to 40 wt % and a modulus of 3.3 to 3.9.
[0019] On the other hand, the present invention also provides the application of the highly flexible modified silicate, wherein the modified silicate solution is used as a film-forming substance for water-based inorganic coatings to prepare water-based inorganic coatings. The raw materials for preparing the water-based inorganic coatings include the following components and the mass percentage of each component is as follows:
[0020]
[0021] The balance is water,
[0022] The sum of the mass percentages of the above components is 100%;
[0023] Furthermore, the polymer emulsion is one or more of pure acrylic emulsion and styrene acrylic emulsion.
[0024] Furthermore, the solid content of the silica sol is 25-35 wt % and the particle size is 20-60 nm.
[0025] Furthermore, the pigment is an inorganic pigment such as zinc white, titanium white, aluminum powder, copper powder, carbon black, chrome yellow, iron blue, cadmium red, cadmium yellow, lead powder, carbon black, iron oxide red, iron oxide yellow, etc.
[0026] Furthermore, the inorganic filler is a mixture of one or more of calcined kaolin, calcium carbonate (heavy calcium carbonate, light calcium carbonate), barium sulfate, slip, white carbon black, mica powder, titanium dioxide, etc.; the fineness of the inorganic filler is 600-1400 mesh.
[0027] Furthermore, the thickener is one or a combination of hydroxyethyl cellulose, organic clay and bentonite.
[0028] Furthermore, the stabilizer is a quaternary ammonium salt stabilizer;
[0029] The auxiliary agent includes at least one of a dispersant and a defoamer; the dispersant is preferably an unsaturated carboxylic acid polymer and its salt; the defoamer is preferably a mineral oil defoamer or an organosilicon defoamer or a combination of the two. The dispersant accounts for 0.3% to 0.5% of the total mass of the coating, and the defoamer accounts for 0.1% to 0.5% of the total mass of the coating.
[0030] The present invention also provides a method for preparing the water-based inorganic coating, which specifically comprises the following steps:
[0031] (1) Add water to the dispersion tank, add thickener, stir until dissolved evenly, add additives and adjust the pH value to 8-10, and continue stirring evenly;
[0032] (2) Add inorganic fillers and pigments, stir until they are evenly dispersed, and the fineness of the scraper test after stirring is ≤50 microns;
[0033] (3) Add polymer emulsion, silica sol, highly flexible modified silicate and stabilizer in sequence and mix well to obtain water-based inorganic coating.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The present invention modifies silicate by polyamine polymer, epoxy silane and alkyl silane to improve the film-forming flexibility of silicate and its compatibility with polymer emulsion. Among them, the solubility of polyamine polymer in high-alkali and high-salt silicate solution is higher than that of other hydrophilic polymers (such as polyacrylic acid, polyvinyl alcohol, polyethylene glycol, etc.), and a higher addition amount can be used. It has a lower glass transition temperature (<-20°C), and the flexibility of the coating is significantly improved; epoxy silane can react with polyamine polymer and silicate anion at the same time to connect silicate with polymer to form a cylindrical organic-inorganic composite structure with silicate as the outer layer structure and polyamine polymer as the inner layer structure, thereby improving the film-forming flexibility of silicate. The alkyl segment structure of alkyl silane can improve the compatibility between modified silicate and polymer emulsion by utilizing the similar dissolution principle between alkyl segment and polymer emulsion. Alkyl silane forms bonds on the surface of silicate particles, enhancing the hydrophobicity of the silicate coating, improving the adaptability of the inorganic coating to the construction environment, and extending the service life of the paint film.
[0036] (2) The highly flexible modified silicate in the present invention uses silicate solution, epoxysilane and alkylsilane as reaction raw materials, and the process is simple and the cost is low. The highly flexible modified silicate is applied to water-based inorganic coatings, which has good film-forming properties, fast drying speed, strong crack resistance and good hydrophobicity. Even without adding polymer emulsion, it still has good film-forming properties and crack resistance, and has good surface hydrophobicity. DETAILED DESCRIPTION
[0037] In the following, in conjunction with the embodiments of the present invention, the technical scheme of the present invention is clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. In the embodiments of the present invention, those who do not specify specific conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. Those who do not specify the manufacturer of the reagents or instruments used in the embodiments are all conventional products that can be obtained commercially.
[0038] Synthesis Example 1
[0039] Dissolve polyethyleneimine (Mw=2000kg / mol, 1.0g) in water, add 300g potassium silicate solution (mass fraction: 30wt%) with a modulus of 3.6, stir for 20 minutes, and heat to 50°C; slowly drop 5g of γ-glycidyloxypropyltriethoxysilane into the above solution, react for 2.5 hours, and then drop 1.1g of n-propyltrimethoxysilane; continue the reaction for 2 hours to obtain a highly flexible modified silicate solution A1 with a solid content of 35.6% and a measured viscosity of 35KU (the viscosity is measured using a rotational viscometer NDJ-9S).
[0040] Synthesis Example 2
[0041] Dissolve polyethyleneimine (Mw=8000kg / mol, 1.8g) in water, add 300g potassium silicate solution (mass fraction: 30wt%) with a modulus of 3.6, stir for 20 minutes, and heat to 80°C; slowly add 6.3g γ-glycidyloxypropyltrimethoxysilane dropwise to the solution, react for 2 hours, and then add 1.2g chloropropyltrimethoxysilane dropwise; continue the reaction for 2 hours to obtain a highly flexible modified silicate solution A2 with a solid content of 36% and a measured viscosity of 43KU.
[0042] Synthesis Example 3
[0043] Dissolve polyallylamine hydrochloride (Mw=4000kg / mol, 0.2g) in water, add 300g potassium silicate solution (mass fraction: 30wt%) with a modulus of 3.6, stir for 20 minutes, and heat to 60°C; slowly drop 1.0g of γ-glycidyloxypropyltriethoxysilane into the above solution, react for 4 hours, drop 0.3g of chloropropyltriethoxysilane and 0.2g of n-propyltriethoxysilane; continue to react for 4 hours to obtain highly flexible modified silicate solution A3 with a solid content of 36% and a measured viscosity of 41KU.
[0044] Synthesis Example 4
[0045] Dissolve polyallylamine (Mw=1000kg / mol, 1.5g) in water, add 300g potassium silicate solution (mass fraction: 30wt%) with a modulus of 3.6, stir for 20 minutes, and heat to 50°C; slowly drop 2g of γ-glycidyloxypropylmethyldimethoxysilane into the above solution, react for 2 hours, drop 0.5g of n-propyltrimethoxysilane and 0.6g of chloropropyltrimethoxysilane; continue to react for 2 hours to obtain a highly flexible modified silicate solution A4 with a solid content of 35.7% and a measured viscosity of 37KU.
[0046] Comparative Synthesis Example 1
[0047] Dissolve polyethyleneimine (Mw=2000kg / mol, 1.0g) in water, add 300g potassium silicate solution (30wt%, 100g) with a modulus of 3.6, stir for 20 minutes, and then heat to 50°C; slowly add 5g of γ-glycidyloxypropyltriethoxysilane dropwise to the above solution, react for 2.5 hours to obtain a modified silicate solution B1 with a solid content of 35% and a measured viscosity of 36KU.
[0048] Comparative Synthesis Example 2
[0049] A potassium silicate solution (30wt%, 100g) with a modulus of 3.6 was stirred for 20 minutes and then heated to 50°C; 5g of γ-glycidyloxypropyltriethoxysilane was slowly added dropwise to the above solution. After reacting for 2 hours, a modified silicate solution B2 was obtained with a solid content of 35.6% and a measured viscosity of 45KU.
[0050] Application Examples
[0051] The highly flexible modified silicate prepared in the above-mentioned synthesis examples 1-4 and the synthesis comparative examples 1-2 is used to prepare water-based inorganic coatings. The raw material manufacturers and models in the application examples and the application comparative examples are as follows: styrene-acrylic emulsion is Badfu RS-837A, pure acrylic emulsion is Baolijia BLJ-960, silica sol is Aorun Chemical S307, titanium dioxide is DuPont Ti-Pure R-960, dispersant is Kain Chemical W28, defoamer is San Nopco SN-Defoamer 154, hydroxyethyl cellulose is Lotte B30K, bentonite manufacturer is Shandong Yonglian, quaternary ammonium salt stabilizer is Aorun Chemical SS1; other raw materials not specified are conventional commercial products.
[0052] The preparation method of the water-based inorganic exterior wall coating in each application embodiment comprises the following steps:
[0053] (1) Add deionized water to the dispersion tank, adjust the speed to 300-500 r / min, add thickener, stir until dissolved evenly, increase the speed to 600-800 r / min, add the additive and adjust the pH value to 8-10, and continue stirring for 5-10 minutes;
[0054] (2) Add inorganic fillers and pigments, stir until evenly dispersed, adjust the speed to 1000-1300 r / min, stir for 15-20 minutes until evenly dispersed, and after stirring, the scraper test fineness is ≤50 microns;
[0055] (3) Adjust the speed to 800-1000 r / min, add polymer emulsion, silica sol, highly flexible modified silicate and stabilizer in sequence, and stir for 5-10 minutes to obtain water-based inorganic exterior wall coating.
[0056] The composition and percentage of each raw material in each application example and application comparative example are shown in Table 1 below:
[0057] Table 1 Raw material composition and percentage content of each application example and application comparison example
[0058]
[0059]
[0060] Application Comparative Example 1
[0061] The water-based inorganic exterior wall coating prepared in this application comparison example is based on the setting of application example 1. The difference between it and application example 1 is that modified silicate solution B1 is used instead of highly flexible modified silicate solution A1, and the rest is consistent with application example 1.
[0062] Application Comparative Example 2
[0063] The water-based inorganic exterior wall coating prepared in this application comparison example is based on the setting of application example 1. The difference between it and application example 1 is that modified silicate solution B2 is used instead of highly flexible modified silicate solution A1, and the rest is consistent with application example 1.
[0064] Application Comparative Example 3
[0065] The water-based inorganic exterior wall coating prepared in this application comparison example is based on the setting of application example 1. The difference between it and application example 1 is that unmodified silicate solution is used instead of highly flexible modified silicate solution A1, and the rest is consistent with application example 1.
[0066] Test Case
[0067] The present invention performs performance tests on the coatings described in application examples 1-7 and application comparison examples 1-3, respectively, and measures the thermal storage stability, low temperature storage stability (3 times), scrub resistance, water resistance, acid resistance, temperature change resistance, stain resistance and artificial aging resistance of the coatings with reference to the industry standard JG / T 26-2002 "Exterior wall inorganic architectural coatings". Films are made according to thin-coating water-based coatings, and the water vapor permeability of the coating film is measured with reference to the industry standard JG / T 309-2011 "Determination and classification of water vapor permeability of exterior wall coatings"; the flexibility of the coating film is measured with reference to the national standard GB / T 6742-2007 "Bending test for paints and varnishes (cylindrical axis)"; the flammability of the dry coating film is measured with reference to the national standard GB 8624-2012 "Classification of combustion performance of building materials and products"; and the mildew resistance of the coating film is measured with reference to the national standard GB / T 1741-2020 "Determination of mildew resistance of paint films". The cement board with exterior wall putty was used, and the exterior wall penetrating primer was rolled on the putty. The inorganic exterior wall coatings of Application Examples 1-7 and Comparative Examples 1-3 were brushed, and the coating amount was about 200g / m 2 After the paint film is completely dried at room temperature, the properties of the paint film are observed and rated on a scale of 0-5. The paint film without cracking or peeling is rated as level 0, and severe cracking or peeling is rated as level 5. The test results are shown in Table 3.
[0068] Table 2 Key performance data of inorganic exterior wall coating samples
[0069]
[0070]
[0071] As shown in Table 2, the performance of the coatings described in Application Examples 1-7 meets the main performance indicators of the industry standard JG / T 26-2002 "Exterior Inorganic Architectural Coatings"; the water vapor permeability of the coating film can reach the level I (higher) specified in the industry standard JG / T 309-2011 "Determination and Classification of Water Vapor Permeability of Exterior Wall Coatings"; the mildew resistance of the coating film can reach the level 0 specified in GB / T 1741-2020 "Determination of Mildew Resistance of Paint Films". However, the inorganic exterior wall coatings using unmodified or partially modified silicates in Comparative Examples 1-3 have poor stability, obvious thickening after hot storage, and a certain amount of peeling and flaking after the coating is completely dried at room temperature. By comparing Application Example 1 with Comparative Examples 1-3, it can be seen that the composite system of polyamine polymer and glycidyl ether oxypropyl siloxane has a greater effect on the flexibility of the coating, while the use of alkyl siloxane can improve the water resistance and scrub resistance of the coating. By comparing Application Example 1 with Application Example 5, it can be seen that the highly flexible modified silicate coating can still effectively form a film without using a polymer emulsion, and this method can effectively reduce the powdering and discoloration phenomenon of the exterior wall coating during the aging process. The above results show that the inorganic coating prepared by the modified potassium silicate of the present invention has good storage stability, weather resistance, non-flammability, mildew resistance and crack resistance.
[0072] The above embodiments are only some embodiments of the present invention, but the purpose of the present invention is not limited thereto. Any changes or modifications made by any technician in the field of the present invention are all covered by the patent scope of the present invention.
Claims
1. A highly flexible modified silicate, characterized in that: The product is prepared by reacting a polyamine polymer, epoxy silane and silicate, and then hydrophobically modifying the surface of the product with an alkyl silane; wherein the epoxy group in the epoxy silane reacts with the amine group in the polyamine polymer, the silanol group in the epoxy silane reacts with the silanol group in the silicate, and the alkyl silane reacts with the hydroxyl group on the surface of the silicate particles to form a hydrolysis condensation reaction; The polyamine polymer is a primary amine or secondary amine polymer; The epoxysilane is an alkoxysilane containing a glycidyl ether structure; The alkylsilane is a trialkoxysilane; The mass ratio of the polyamine polymer to epoxy silane is 1:1 to 1:6; the mass ratio of the polyamine polymer, alkyl silane and silicate is 0.2 to 2:0.5 to 1.5:
100.
2. The highly flexible modified silicate according to claim 1, characterized in that: The average viscosity of the highly flexible modified silicate is 30 to 50 KU.
3. The highly flexible modified silicate according to claim 1, characterized in that: The polyamino polymer is one or more of polyethyleneimine, polyallylamine and derivatives thereof, and has a molecular weight of 400 to 9000 kg / mol.
4. The highly flexible modified silicate according to claim 1, characterized in that: The epoxysilane is one or more of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-glycidyloxypropyltriisopropoxysilane, γ-glycidyloxypropylmethyldimethoxysilane or γ-glycidyloxypropylmethyldiethoxysilane.
5. The highly flexible modified silicate according to claim 1, characterized in that: The structural formula of the alkylsilane is R 1 Si(OR 2 )3, where R 1 is an alkyl group with no more than 4 carbon atoms, R 2 It is methyl or ethyl.
6. The highly flexible modified silicate according to claim 1 or 5, characterized in that: The alkylsilane is one or more of methyltrimethoxysilane, methyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, chloropropyltrimethoxysilane or chloropropyltriethoxysilane.
7. The highly flexible modified silicate according to claim 1, characterized in that: The silicate is sodium silicate or potassium silicate.
8. The method for preparing the highly flexible modified silicate according to any one of claims 1 to 7, characterized in that: The specific steps include: The polyamine polymer is dissolved in water, and a silicate solution is added thereto, mixed evenly and heated to 40-80° C.; epoxy silane is added, reacted for 2-4 hours, and then alkyl silane is added, and the reaction is continued for 2-4 hours to obtain the aqueous solution of the highly flexible modified silicate.
9. The preparation method according to claim 1, characterized in that: The silicate solution has a solid content of 20 to 40 wt % and a modulus of 3.3 to 3.
9.
10. A water-based inorganic coating, characterized in that: The raw materials for its preparation include the highly flexible modified silicate described in any one of claims 1 to 7 or the highly flexible modified silicate prepared by the preparation method described in any one of claims 8 to 9.
11. The water-based inorganic coating according to claim 10, characterized in that: The raw materials for its preparation include the following components and the mass percentage of each component is as follows: The balance is water, The sum of the mass percentages of the above components is 100%; 12. The water-based inorganic coating according to claim 11, characterized in that: The polymer emulsion is one or more of pure acrylic emulsion and styrene acrylic emulsion.
13. The water-based inorganic coating according to claim 11, characterized in that: The solid content of the silica sol is 25-35wt% and the particle size is 20-60nm; the pigment is one of zinc white, titanium white, aluminum powder, copper powder, carbon black, chrome yellow, iron blue, cadmium red, cadmium yellow, lead powder, carbon black, iron oxide red and iron oxide yellow; the inorganic filler is a mixture of one or more of calcined kaolin, calcium carbonate, barium sulfate, slip, white carbon black, mica powder, titanium dioxide, etc.; the thickener is one or a combination of several of hydroxyethyl cellulose, organic clay and bentonite; the stabilizer is a quaternary ammonium salt stabilizer.
14. The water-based inorganic coating according to claim 13, characterized in that: The inorganic filler has a fineness of 600 to 1400 meshes.
15. The water-based inorganic coating according to claim 11, characterized in that: The auxiliary agent includes at least one of a dispersant and a defoamer; the dispersant is an unsaturated carboxylic acid polymer and its salt; the defoamer is one or a combination of a mineral oil defoamer or an organosilicon defoamer; wherein the dispersant accounts for 0.3% to 0.5% of the total mass of the coating, and the defoamer accounts for 0.1% to 0.5% of the total mass of the coating.
16. The method for preparing the water-based inorganic coating according to any one of claims 10 to 15, comprising the following steps: (1) Add water to the dispersion tank, add thickener, stir until dissolved evenly, add additives and adjust the pH value to 8-10, and continue to stir evenly; (2) Add inorganic fillers and pigments, stir until they are evenly dispersed, and the fineness of the scraper test after stirring is ≤50 microns; (3) Add polymer emulsion, silica sol, highly flexible modified silicate and stabilizer in sequence and mix well to obtain water-based inorganic coating.
Citation Information
Patent Citations
Inorganic coating as well as preparation method and application thereof
CN113881259A
Antiviral inorganic coating and preparation method thereof
CN114196243A
Acrylic acid-potassium silicate copolymer emulsion, preparation and application thereof, breathable flame-retardant weather-resistant exterior wall inorganic coating and preparation thereof
CN115124666A
Cited By
Low-VOC environment-friendly building interior wall coating composition and preparation method thereof
CN122278269A